Two New Terpenoids from Talaromyces purpurogenus - Wang, Wenjing (Mar Drugs, 2018)
A new sesquiterpenoid 9,10-diolhinokiic acid (1) and a new diterpenoid roussoellol C (2), together with 4 known compounds, were isolated from the extracts of laboratory cultures of marine-derived fungus Talaromyces purpurogenus. 9,10-diolhinokiic acid is the first thujopsene-type sesquiterpenoid containing a 9,10-diol moiety, and roussoellol C possesses a novel tetracyclic fusicoccane framework with an unexpected hydroxyl at C-4. These new structures were confirmed by spectroscopic data, chemical method, NMR data calculations and electronic circular dichroism (ECD) calculations. The selected compounds were evaluated for cytotoxicities against five human cancer cell lines, including SW480, HL-60, A549, MCF-7, and SMMC-7721 and the IC(50) values of compound 2 against MCF-7 and 3 against HL-60 cells were 6.5 and 7.9 μM, respectively.